Participatory forest management: analyzing livelihood assets of forest users in North-West Frontier Province of Pakistan - Shahbaz, Babar; Ali, Tanvir; Suleri, Abid Qaiyum (Nepal Journal of Forestry, 2008)
Forest depletion is one of the most severe issues for Pakistan, which has resulted in many environmental and economical problems such as landslides, soil erosion, floods, soil degradation and displacement of people etc. Forests are an important natural capital, which is supposed to contribute towards achieving sustainable livelihoods reducing poverty. The ongoing trend of deforestation has a negative impact not only on production and protection functions of the forests but also on the livelihoods of those who live in and around the forest management, the Government of Pakistan has initiated a forestry reform process which aimed to reduce forest depletion by involving stakeholders in forest management. This paper attempts to analyze the livelihood assets of forest dependent people living in North-West Frontier Province (NTFP) of Pakistan in context with participatory approach in forest management. Keywords: Participatory Forest Management, Pakistan, Livelihood, Forest Users